Field tests of a participatory ergonomics toolkit for Total Worker Health - Nobrega, Suzanne; Kernan, Laura; Plaku-Alakbarova, Bora; Robertson, Michelle; Warren, Nicholas; Henning, Robert (Applied ergonomics, 2017)
Growing interest in Total Worker Health® (TWH) programs to advance worker safety, health and well-being motivated development of a toolkit to guide their implementation. Iterative design of a program toolkit occurred in which participatory ergonomics (PE) served as the primary basis to plan integrated TWH interventions in four diverse organizations. The toolkit provided start-up guides for committee formation and training, and a structured PE process for generating integrated TWH interventions. Process data from program facilitators and participants throughout program implementation were used for iterative toolkit design. Program success depended on organizational commitment to regular design team meetings with a trained facilitator, the availability of subject matter experts on ergonomics and health to support the design process, and retraining whenever committee turnover occurred. A two committee structure (employee Design Team, management Steering Committee) provided advantages over a single, multilevel committee structure, and enhanced the planning, communication, and teamwork skills of participants. •Iterative design of a toolkit for a participatory Total Worker Health® program.•Participatory ergonomics is used to create integrated TWH interventions in 7 steps.•Separate employee design teams offer advantages over a single multi-level committee.•Subject matter experts on ergonomics and health are essential during design process.•Re-training of team members is crucial for program effectiveness and sustainability.